Tactics of the Human Experimental Technics in American Fiction - Shackelford, Laura (University of Michigan Press, 2015)
Tactics of the Human: Experimental Technics in American Fiction examines the comparative perspective on digital cultures contemporary American fiction develops through the creative transposition of digital rhetorics and technological practices -such as the hyperlink, network, or recursive processing - into print or in translating a classic print narrative into a digital hypertext fiction. These literary experiments with early digital cultures of the 1990's comparatively retrace and speculate on the digital's transformative influence on prior understandings of the human, her social life, and her relations to material lifeworlds, exploring the consequences of the apparent plasticity of the boundaries of the human, particularly for women, subaltern subjects, and others already considered liminally human. As they query the digital technics entering into textual practices, subjectivity, spatial practices and social networks, lived space, nation, and economic circulation these texts reconceive their own literary print narrative methods and material modes of circulation in order to elaborate on unnoticed potentialities and limits of digital technics, providing a crucial means to reorient digital cultures of the present.